Treatment patterns in non-small-cell lung cancer in China: Results from the CancerMPact survey 2020. (2021) - Durbin, Laura; Murali, Bhavna; Li, Song; Zhao, Linda; Hawthorne, Stephanie; Kanas, Gena; Davis, Christine; Clark, Otávio
Highlights: Chinese physicians favor adjuvant therapy over neoadjuvant/peri‑operative in NSCLC. At least one biomarker test is performed in 75% of the patients. Platinum-based regimens are preferred in the first-line setting in China. 30% of SQ/18% of NSQ NSCLC PD-L1≥50% patients were treated with a PD-1/L1 inhibitor. Abstract: Purpose: To report the treatment patterns of non-small-cell lung cancer (NSCLC) patients in China based on a survey of physicians (CancerMPact). Methods: 117 Chinese physicians from 27 cities in mainland China were recruited for an online survey in October 2020, reporting on how they treat their patients across all disease stages, including histology and relevant biomarkers in advanced or metastatic NSCLC. Results: Surveyed physicians indicated that almost half of their stage I patients were treated with surgery only. For stage II patients, it is more common to treat with surgery in combination with radiation and/or systemic therapy (44.5%), whereas the use of surgery decreases for stage III patients and the overall use of systemic therapy increases (63.4%-68.8%). Physicians are more likely to use systemic therapy alone for stage IV patients (31.4%). Chosen treatment regimens for stage IV NSCLC varied by histology and biomarkers, and several observed treatment patterns differed from the USA. In China, platinum-based chemotherapy is standard of care for treating stage IV NSCLC patients, unlike the USA, where checkpoint inhibitors are the dominant choice in first-line. Further, Chinese physicians reported prescribing biomarker-targeted agents for one-third or less of their patients with EGFR, ALK, ROS-1, or BRAF driver mutations, compared to 60–95% in the USA. Conclusion: As treatment options expand in NSCLC in China, physicians face complex decisions for the treatment of their patients. Treatment patterns often vary, including by disease histology and clinically relevant biomarkers. The standard of care for NSCLC in China also differs from the USA.